1998
DOI: 10.1111/j.1600-051x.1998.tb02429.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of different root debridement modalities in open flap surgery

Abstract: It is unclear what degree of roughness or smoothness result from use of hand instruments alone in comparison to the use of hand instruments in combination with other aids and how it may effect the grade of cleanliness. The aim of this study was to determine in vivo whether the combination of hand instruments with other aids can increase the effectiveness of root debridement. 11 patients with holpless 4 mandibular incisors were involved in this study. After elevating a lingual and buccal mucoperiosteal flap, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 34 publications
3
31
0
1
Order By: Relevance
“…Often, root surface instrumentation with hand instruments (HIs) is difficult, time consuming, and requires a substantial amount of physical effort. In addition to HIs, various powered instruments are available to the clinician for mechanical root preparation, including sonic and ultrasonic scalers and rotating instruments 2,5‐13 . Sonic and ultrasonic instruments are valuable because they do not require as much physical effort by the operator 14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Often, root surface instrumentation with hand instruments (HIs) is difficult, time consuming, and requires a substantial amount of physical effort. In addition to HIs, various powered instruments are available to the clinician for mechanical root preparation, including sonic and ultrasonic scalers and rotating instruments 2,5‐13 . Sonic and ultrasonic instruments are valuable because they do not require as much physical effort by the operator 14 .…”
mentioning
confidence: 99%
“…Sonic and ultrasonic instruments are valuable because they do not require as much physical effort by the operator 14 . Although each of these instruments has shown clinical effectiveness, none has proven the most effective in most clinical situations where short application times are required to remove plaque, calculus, and diseased tooth structures while leaving a relatively smooth root surface 13,15‐19 …”
mentioning
confidence: 99%
“…Scanning electron microscope studies concentrating on the quality of the instrumented surface achieved seem to support their use (11,24,25). While the findings from these studies have been mostly qualitative (SEM analysis) or semi-quantitative (RLTSI, Roughness and Loss of Tooth Substance Index), one study (11) also provided quantitative (profilometric) data showing no significant difference in surface roughness between a diamond-coated bur and Gracey curettes.…”
Section: Discussionmentioning
confidence: 99%
“…It must also be assumed that these other instruments operated under a similar limitation (indeterminate degree of contact) when applied to an in vivo site, where past studies have shown their level of efficacy both through the proxy parameters of decrease probing pocket depth and bleeding on probing, as well as the superficial physical characteristics of surface roughness and depth of defects after extraction of experimentally treated, but not-rational-to-keep periodontally involved teeth (16,24,25,29).…”
Section: Discussionmentioning
confidence: 99%
“…Many in vivo studies of new devices for periodontal therapy have claimed to investigate the potential of these devices, but they also relied on the judgement of the dentist, who scanned and subsequently treated the root surfaces until he considered it to be clean. After extraction, the residual deposits were assessed (Yukna et al 1997, Huerzeler et al 1998, Kocher et al 2002, Geisinger et al 2007). Thus, in addition to the equipment used, the skills and experience of the dentist markedly influenced the final outcome, if this approach is followed.…”
Section: Discussionmentioning
confidence: 99%